Pancreatic cancer (Problems in general surgery, 1997)
Includes chapters on the management of patients with pancreatic cancer as experienced at Johns Hopkins, Massachusetts General Hospital, Mayo Clinic, M.D. Anderson, Memorial Sloan-Kettering, Virginia Mason, and in the United Kingdom and Japan.